Reframing Islamic Education in the Post-Truth Era: Integrating Islamic Epistemology and Digital Ethics through Tabayyun Literacy - Mukaromah, Muhimmatul; Janah, Septa Miftakul; Bin Ahmad, Muhammad Anwar (Program Studi Pendidikan Agama Islam, 2026)
This article aims to examine how Islamic education can be reframed in response to the epistemic challenges of the post-truth era through the integration of Islamic epistemology and digital ethics via tabayyun literacy. It seeks to conceptualize tabayyun literacy as an epistemological framework for reconstructing digital literacy within the broader project of Islamization of knowledge. The research method used was qualitative library research with a conceptual-analytical approach. Data were derived from primary Islamic sources, particularly relevant Qur’anic verses and classical interpretations, as well as contemporary scholarly literature on Islamic epistemology, digital information ethics, critical media literacy, and post-truth discourse. The data were analyzed through thematic interpretation and integrative conceptual synthesis. The results of the study show that tabayyun literacy functions as an integrative epistemological framework that operationalizes the Islamic synthesis of revelation (wahy), reason (‘aql), and empirical verification in digital information practices. The findings indicate that tabayyun literacy extends digital literacy beyond technical verification by embedding moral accountability, epistemic vigilance, and critical reflection into information engagement. The study further demonstrates that integrating Islamic epistemology and digital ethics through tabayyun literacy contributes to reframing Islamic education from a transmissive model of knowledge delivery toward an epistemic-formative model centered on critical inquiry and ethical reasoning. This study concludes that tabayyun literacy provides a coherent conceptual foundation for renewing Islamic education in the post-truth era, enabling it to remain intellectually relevant, ethically grounded, and responsive to the challenges of digitally mediated societies.